Re: Ashley M. Hopkins, Ganessan Kichenadasse, Christos S. Karapetis, et al. Concomitant Proton Pump Inhibitor Use and Survival in Urothelial Carcinoma Treated with Atezolizumab. Clin Cancer Res. In press. https://doi.org/10.1158/1078-0432.CCR-20-1876 - Satoshi Funada; Takashi Yoshioka; Yan Luo (European Urology Oncology, 2020)
In March 2026, Ipsen voluntarily withdrew the EZH2 inhibitor tazemetostat (Tazverik) from all markets and indications following results from the confirmatory Phase Ib/III SYMPHONY-1 trial demonstrating hematologic second primary malignancies (SPMs) in 5.7% of treated patients, compared with none in the control arm. The most frequently reported SPMs were myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML). Although this finding may be interpreted as an idiosyncratic liability of a single agent, the biology of EZH2 suggests a broader, target-driven risk. EZH2 functions in a context-dependent manner as both an oncogene and a tumor suppressor. Gain-of-function mutations drive transformation in germinal center B-cell lymphomas, whereas loss-of-function alterations impair hematopoietic stem cell differentiation and are recurrent in myeloid malignancies, including MDS and AML. In selected solid tumor contexts, such as specific subtypes of medulloblastoma, EZH2 loss can likewise promote tumorigenesis. These observations raise concern that chronic pharmacologic inhibition of EZH2 may phenocopy loss-of-function states that initiate myeloid neoplasia. We argue that the withdrawal of tazemetostat exposes a fundamental vulnerability in the development of epigenetic therapies: target validation has focused on tumor-intrinsic effects while underweighting consequences in normal stem cell compartments. This issue is particularly relevant for ongoing Phase III programs in prostate cancer, where prolonged exposure may amplify latency-dependent risks. We propose changes to preclinical safety assessment, trial design, and pharmacovigilance to mitigate predictable, target-mediated toxicities.